Variable structure wireless power transfer converter with misalignment tolerant - Zhilei Yao; Yiming Zhang (International Journal of Electrical Power & Energy Systems)
Misalignment of the secondary coil relative to the primary coil is inevitable in the wireless power transfer (WPT) converter, which decreases the transmission power and the system efficiency. Moreover, constant current (CC) and constant voltage (CV) control methods should be used to improve the charging efficiency of the battery. Thus, a WPT system based on TS/S-SP (T-order series/series − series and parallel compensation) hybrid compensation network is proposed. The system can transfer between the CC mode and the CV mode by controlling two switches. The CC and CV modes can be realized by the TS-SP and S-SP compensation networks. Operating principles of the proposed converter in both modes are elaborated. The misalignment tolerant ability is compared with other existing resonance networks. Finally, the theoretical analysis is confirmed by simulation and experimental results. When longitudinal axis misalignment of the coupler changes by 1/5, the output voltage fluctuation in the CV mode is only 1.06 % under Z- misalignment and 2.5 % under Y- misalignment. The output current fluctuation in the CC mode is 4.7 % under Z- misalignment and 4.53 % under Y- misalignment. Efficiency of the WPT converter is above 90 % in both CC and CV modes. The seamless transfer can be achieved from CC to CV modes.